2018
DOI: 10.1186/s41155-018-0102-3
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Brief-COPE for the evaluation of coping strategies in the Chilean population

Abstract: The Brief-COPE is an abbreviated version of the COPE (Coping Orientation to Problems Experienced) Inventory, a selfreport questionnaire developed to assess a broad range of coping responses. Currently, it is one of the best validated and most frequently used measures of coping strategies. The aim of this study was to validate a culturally appropriate Chilean version of the Brief-COPE, assess its psychometric properties and construct and congruent validity. The Spanish version of the Brief-COPE was administrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
160
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(210 citation statements)
references
References 32 publications
19
160
1
3
Order By: Relevance
“…Instead, dimensions that are considered to be less adaptive (self-distraction, venting, behavioral disengagement, denial, substance abuse, self-blame, and humor) had α = 0.761. Such results confirm that Brief COPE is a valid and psychometrically sound instrument for measuring coping strategies (García et al 2018).…”
Section: Assessment Of the Coping Orientation To Problems Experiencedsupporting
confidence: 77%
“…Instead, dimensions that are considered to be less adaptive (self-distraction, venting, behavioral disengagement, denial, substance abuse, self-blame, and humor) had α = 0.761. Such results confirm that Brief COPE is a valid and psychometrically sound instrument for measuring coping strategies (García et al 2018).…”
Section: Assessment Of the Coping Orientation To Problems Experiencedsupporting
confidence: 77%
“…which was similarly reported in previous validation studies including the original Brief-COPE study (Charles S. Carver, 1997;García et al, 2018;Monzani et al, 2015;Su et al, 2015). Nevertheless, the developer of Brief-COPE reported that the exibility of the inventory encourage researchers to apply and test on different settings and population to extensively either using all the subscales or selectively use relevant scales in their research (Charles S. Carver, 1997).…”
Section: Discussionsupporting
confidence: 54%
“…Following sound theoretical guidance, a number of health-relevant studies have provided empirical evidences by using statistical tools to extract underlying domains and test psychometric properties in various settings and populations such as caregivers of people with dementia in the United Kingdom (Cooper, Katona, & Livingston, 2008), among breast cancer chemotherapy patients in Malaysia (Yusoff, Low, & Yip, 2009), people with traumatic brain injury in New Zealand (Snell, Siegert, Hay-Smith, & Surgenor, 2011), people living with HIV in China (Su et al, 2015), person living with HIV/AIDS in India (Mohanraj et al, 2015), pregnant minority women in the United States (Ruiz et al, 2015), adults in Italy (Monzani et al, 2015), and community population in Chile (García, Barraza-Peña, Wlodarczyk, Alvear-Carrasco, & Reyes-Reyes, 2018). Brief-COPE is also translated in a number of languages such as French version (Muller & Spitz, 2003), Malay version (Yusoff et al, 2009), Brazilian-Portuguese version (Brasileiro et al, 2016), and Chilean version (García et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…53 A coping style characterised by greater use of social support systems was found to be inversely correlated with cortisol levels in women. 53,54 Further, an active coping strategy of trying to be resilient and in control of stress-provoking situations might have augmented the release of cortisol in our participants.…”
Section: Discussionmentioning
confidence: 85%
“…However, more longitudinal studies are needed to clarify the nature of the correlation between stress and cortisol circadian rhythm in expatriates compared with Emirati women healthcare professionals, as sources, levels of stress and coping styles may differ across ethnic groups. 54 Importantly, the availability of a supportive environment that attracts and supports women who relocate with their families to live and work in the UAE could be an additional reason for our participants' adaptive coping with stress and explain the less fluctuation in cortisol levels. 56 The UAE government has highlighted the happiness of working women (regardless of nationality) as national developmental goal in its 2021 national agenda, including efforts to support them relocate smoothly with their families into the UAE culture.…”
Section: Discussionmentioning
confidence: 97%